Influence of Vestibular Irritation on Stabilometric Indicators of Statokinetic Stability of Football Players - Abdoulakhat S. Chinkin; Andrey S. Nazarenko (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The dynamics of stabilometric indicators of players and non-athletes is considered. It is shown that in the Romberg sample with eyes open and closed disparities in maintaining the balance between players and non-athletes are practically not detected. The most significant shifts of the stabilometric performance we observed in the vestibular stimulation in the Romberg sample with eyes open, which is significantly less than that of the players.